2022
DOI: 10.4251/wjgo.v14.i1.124
|View full text |Cite
|
Sign up to set email alerts
|

Development of artificial intelligence technology in diagnosis, treatment, and prognosis of colorectal cancer

Abstract: Artificial intelligence (AI) technology has made leaps and bounds since its invention. AI technology can be subdivided into many technologies such as machine learning and deep learning. The application scope and prospect of different technologies are also totally different. Currently, AI technologies play a pivotal role in the highly complex and wide-ranging medical field, such as medical image recognition, biotechnology, auxiliary diagnosis, drug research and development, and nutrition. Colorectal cancer (CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 172 publications
(244 reference statements)
0
14
0
Order By: Relevance
“…Without a large amount of high-quality data as the basis, even the most advanced algorithm model will not help. Therefore, we urgently need to standardize big medical data and increase interoperability among multiple centers ( 90 , 147 , 156 ). Moreover, there are specific problems in various imaging omics and AI models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a large amount of high-quality data as the basis, even the most advanced algorithm model will not help. Therefore, we urgently need to standardize big medical data and increase interoperability among multiple centers ( 90 , 147 , 156 ). Moreover, there are specific problems in various imaging omics and AI models.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have confirmed that the da Vinci SP system is an excellent model for taTME and natural orifice specimen extraction ( 139 , 145 , 146 ). One of the biggest problems of robotic surgery is the high cost ( 145 , 147 ). It indicates that the promotion of robotic surgery requires government financial support.…”
Section: The Application Of Ai In Crc Treatmentmentioning
confidence: 99%
“…Another issue with the clinical application of AI and ML is the “black box” problem, in which we are able to see the inputs and outputs of a model, but not the variables that are used by the model to generate those outputs. More efforts are needed to make the algorithms, especially deep learning algorithms, interpretable to clinicians and to allow streamlining of data preprocessing ( 114 ). Additionally, most of the studies have a retrospective design, and more evidence on the effectiveness of AI is needed from multicenter, prospective studies.…”
Section: Clinical Validation Applications Limitations and Future Dire...mentioning
confidence: 99%
“…For example, as a predictive modeling and early detection, AI could be used to analyze data from a variety of sources, such as electronic health records, genetic information, and environmental data, to predict an individual’s risk of developing cancer and to tailor prevention strategies accordingly [ 13 , 14 , 15 , 16 ]. AI-related applications may reduce screening costs [ 17 ], provide more reliable diagnostics [ 13 , 18 , 19 , 20 ], improve prognostics [ 13 , 19 , 21 , 22 , 23 , 24 , 25 ], and aid in the discovery of new drugs [ 14 , 15 ]. Several areas of cancer care are expected to benefit from AI-related applications, including cancer radiology and clinical oncology [ 10 ].…”
Section: Introductionmentioning
confidence: 99%